Armenia Early Childhood Development : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
This report presents an analysis of the early childhood development (ECD) programs and policies that affect young children in Armenia and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the systems approach for better education results (SABER)-ECD framework and includes analysis of early learning, health, nutrition, and social and child protection policies and interventions in Armenia, along with regional and international comparisons. The national program on the protection of children's rights for 2004-2015 is a multi-sectoral ECD policy in Armenia that comprises the education, health, and social protection sectors, and serves as an overarching umbrella to guarantee access to essential ECD services.